Studies on Forest Ecosystems Diversity of Rajaji National Park, Uttar Pradesh in a Conservation Perspective - Singh, K. K; Prakash, Anand (Indian Forester, 1994)
Rajaji National Park is situated in the Siwalik Forest Division, Uttar Pradesh and has an area of approximately 820.40 km2. The diverse forest ecosystems of the park provide an ideal habitat for many wild animals. The forests are classified under the Northern Tropical Moist Deciduous types having varied and diverse ecosystems. A general survey of the forests revealed some important types of plant associations likeShorea, Mallotus and Adina Community Shorea-Terminalia and Bridelia community - Syzygium, Phoebe and Drypetes community etc. Based on the physiopomy and floristic compositions, the forests may be grouped into six types namely (1) Sal forest, (2) Mixed forest, (3) Riverine forest, (4) Scrubland, (5) Grassland (Savannah), (6) Sub-tropical Pine forest. The dominant tree specie. Shorea Robusta Gaertn.f. forms pure belt of Sal forest in major part of the park. Factors affecting, the vegetation and plant-animals interaction have been given in this paper. The diverse tropical ecosystems of the park have many unique characteristics which have both scientific importance and practical significance for overall ecodevelopment. Discussing the depleting, plant resources, the possible causes and effective measures for conservation of threatened species are provided in this paper.